E.FFECT OF HARVESTING TECHNIQUE AND OTHER FACTORS ON · OOCYTE RETRIEVAL IN BUFFALO (BUBALUS BUBALIS) - RAO, M MUTHA; MAHESH, Y UMA (The Indian Journal of Animal Reproduction, 2023)
A study was undertaken to assess the ovarian biometry, follicular population and oocyte rec9very in buffaloovaries obtained from a local abattoir. Three harvesting techniques viz., aspiration, puncture and slicing methodswere employed to recover oocytes. Effect of ovarian status (luteal phase vs. non-luteal phase), ovarian volume(1.5 cm 3), side of ovary {Right vs. left) and number of visible follicles (No follicles vs.1-5 follicles vs:6-1 0 follicles) on oocyte yield and quality were analyzed. The ovarian biometry (length, width, thickness, volumeand weight) and the number of visible follicles did not differ significantly between left and right ovaries. The numberof visible follicles were significantly higher (P1.5 cm3• The results indicate that slicing method issuperior to the other two methods employed in this study to harvest more number of good quality as well as culturegrade oocytes from buffalo ovaries.
Keywords: Oocyte Retrieval; Oocyte recovery; Visible follicles; Buffalo